An updated structure for a stainless steel liner and the estimation of its buckling strength. (February 2018) - Dong, Shun; Zhou, Wei; Zhang, Haifeng; Ma, Baosong
Highlights: An updated structure composed of two or more arch liners was proposed. Based on the Glock's model, the theoretical solution was derived . With Moore's approach, enhancement factor K for the new structure was defined. FEM method was used to check the correctness of the theoretical solution. Abstract: Stainless steel liner has been used for the trenchless rehabilitation of damaged pipelines in China, but its limited buckling strength severely constrains its wider application due to the lack of ring stiffness. The increase of liner thickness to some extent results in a greater buckling strength, but still unavoidably causes a higher cost. With the intention of improving the stability of the thin-wall structure as well as saving project cost at the same time, an updated structure, consisting of numbers of arch liners, was introduced in this paper. Like the conventional circular liner, arch liners are in-situ manually welded to the host pipe to form a cylinder. To predict the buckling strength of rigidly encased arch liners, a theoretical model, modified from Glock's buckling model, was also proposed, based on which the enhancement factor K was defined. With this theoretical model, a series of calculations was done to demonstrate the arch liner's improved stability. Meanwhile, finite-element method (FEM) was used to estimate the buckling strength of arch liners, and the Arc-Length Control Method was applied in the simulation to trace the pre-and post-buckling behavior. Comparison between the theoretical model and FEM results was performed and the excellent agreement showed the model's correctness.